Identification of Notoginseng powder based on similarity to "DNA Barcoding Core-genotype". (4th May 2017) - Song, Xiaona; Li, Yanpeng; Xu, Guojie; Liu, Chunsheng; Liu, Yong; Zhang, Xiaoqin; Liu, Ying; Liu, Siqi; Gu, Xuan
Abstract: Notoginseng powder is a medicine form of Notoginseng radix et rhizoma in Chinese Pharmacopeia. Common adulterants of Notoginseng powder appeared in the market include powder of Panax ginseng and Panax quinquefolius . Here, "DNA Barcoding Core-Genotype (DBCG)" based on ITS sequences was developed for authenticating Notoginseng powder. DBCG was the genotype with the highest frequency of DNA barcoding in species. The DBCG was found as the reference sequence and minimal-similarity to identify species was calculated by large sample analysis. Then we could calculate similarity index between DBCG and sequences of the unidentified Notoginseng powder and compare it through minimal-similarity to identify the species. This method was simple, efficient, and might be a preferable tool for accurate authentication.